Principles of Proteomics
Principles of Proteomics, Second Edition, provides a concise and user-friendly introduction to the diverse technologies used for the large-scale analysis of proteins, as well as their applications, and their impact in areas such as drug discovery, agriculture, and the fight against disease. Proteomics is a fast-advancing field in which researchers seek to capture all the proteins in the cell and characterize them in ever more detail. Principles of Proteomics has been fully updated to reflect the most recent developments in the field without losing its focus on the underlying principles. With worked examples, case studies profiling both established and emerging technologies, and further reading lists for each chapter, Principles of Proteomics is an ideal introduction for students, researchers and those working in the industry.